INTEGRATING LOCAL WISDOM-BASED CHARACTER EDUCATION INTO LANGUAGE TEACHING: A MODEL FOR CULTURAL AND MORAL DEVELOPMENT - Anggraini, Dian; Riyanti, Asih (Universitas Islam Negeri (UIN) Fatmawati Sukarno Bengkulu, 2025)
Character is a positive trait reflected in a person's daily behavior. It is an essential part of one’s personality and social life, although it is sometimes not systematically integrated into education. Therefore, this research aims: 1) To describe the process of integrating local wisdom-based character education values at Baitul Izzah Nganjuk Islamic Junior High School. This research used a qualitative method with a phenomenological approach. There were three research subjects: headmaster of school, teachers and also and seventh grade students at Baitul Izzah Nganjuk Islamic Junior High School. Students were selected using purposive sampling method. Data collection was conducted through in-depth and open-ended interviews, observation, and document analysis. Data analysis was carried out with four steps, namely: collecting data, condensing data, presenting data and finally drawing conclusions. The results of this study show that the process of integrating the value of character education in Language learning used material book. The findings of this study indicate that teachers integrate language learning with materials rooted in local wisdom. Furthermore, throughout the learning process, teachers also model positive behavior that reflects the character values inherent in local wisdom. This integration not only enriches the content of language instruction but also fosters students’ character development by embedding cultural values in everyday classroom practices. As a result, students not only improve their language skills but also internalize important moral and social values grounded in their own cultural heritage. This research is expected to be used as a model and cultural development and also can be used as a reference for other researchers who want to research the value of character education.